Los hábitos de higiene para fortalecer la autoestima de las niñas y niños de 3 a 5 años de edad del nivel inicial I y II de la escuela de educación básica Dr. Reinaldo Espinosa Aguilar de la ciudad de Loja. Período 2014-2015 - Guamán Angamarca, Martha Rocío (2016)
The present research understands a study on the habits of hygiene to strengthen the autoesteem of the girls and children from 3 to 5 years of age of the initial level I and the II of the School of Basic Education Dr. Reinaldo Espinosa Aguilar of Loja's City. Period 2014-215. The general aim of the present investigation is to know since they contribute the habits of hygiene to strengthen the autoesteem of the girls and children. The methods applied for the execution of the present work investigative were: the scientific, analytical synthetic, hermeneutic, statistical method. The technology was the observation. Since we apply instrument the guide of valuation of the infantile autoesteem. The population is integrated by 15 children. With the information obtained of the guide of valuation of the infantile autoesteem we demonstrate the levels of autoesteem that the children show 73 % they present a normal autoesteem whereas 27 % shows an autoesteem down. One concludes that the habits of hygiene are important for the autoesteem, by what there is recommended that the habits of hygiene must interfere from the first years of the infancy, when the personality of the child is more permeable and the acquisition of the practices and customs related to the health it is possible to do in gradual form